An Analysis of the Level of Development in Malang Regency Based on a Typology of Development Regions - Zulfikar Mohamad Yamin Latuconsina; Ernan Rustiadi; Sahara Sahara (Journal of Regional and City Planning, 2018)
Abstract. A regionalization approach seeks to manage and to achieve development goals in line with regional characteristics. The development system of Malang Regency is conducted through regionalization approach that divided the area into six development regions (DR). Considering that each region has diverse characteristics/typology, describing this typology is the key to map the conditions and problems and to formulate alternative solutions. Thus, the main objective of the research is to analyze the development level of Malang Regency based on a typology of development regions. The specific objectives are as follows: (1) Analyzing the economic diversification in the development regions; (2) Analyzing the hierarchy of development regions; and (3) Analyzing the level of accessibility of the development regions. The research methods include entropy diversity index, scalogram, the level of accessibility (road density index and connectivity index) and cluster analyses. The results show that cluster analysis with proportional and comprehensive variables is able to describe the typology of development regions of Malang Regency, which are divided into three clusters, i.e.: (1) DR I  Malang City Ring as the only cluster with a has high development level, (2) DR II Kepanjen, DR IV Tumpang, WP V Turen and Dampit have a medium development level (3) DR III Ngantang and DR VI Sumbermanjing Wetan have a low development level.Keywords. Regional development, regionalization approach, regional typology, development region.Abstrak. Pendekatan perwilayahan merupakan salah satu pendekatan untuk mengelola dan mencapai tujuan pembangunan sesuai dengan karakteristik wilayah. Sistem pembangunan Kabupaten Malang dilakukan melalui pendekatan perwilayahan yakni dengan membagi Kabupaten Malang menjadi 6 wilayah pengembangan. Mengingat setiap wilayah pengembangan mempunyai karakteristik/tipologi yang cenderung berbeda-beda maka upaya penggambaran tipologi ini menjadi kunci untuk memetakan kondisi dan permasalahan sekaligus merumuskan alternatif solusi. Tujuan utama penelitian adalah menganalisis tingkat pembangunan Kabupaten Malang berbasis tipologi wilayah pengembangan. Adapun yang menjadi tujuan antara adalah: (1) Menganalisis keragaman sektor perekonomian wilayah pengembangan, (2) Menganalisis hierarki wilayah pengembangan, dan (3) Menganalisis tingkat aksesibilitas wilayah pengembangan.  Beberapa teknik analisis digunakan yaitu indeks diversitas entropi, skalogram, tingkat aksesibilitas wilayah (indeks kerapatan jalan dan indeks konektivitas) dan analisis gerombol/klaster. Hasil penelitian menunjukkan  bahwa: analisis gerombol/klaster menggunakan variabel yang lebih komprehensif dan proporsional mampu menggambarkan tipologi wilayah pengembangan Kabupaten Malang secara lebih baik, yang terbagi kedalam 3 klaster, yaitu: (1) WP I Lingkar Kota Malang sebagai klaster tersendiri dengan tingkat perkembangan maju, (2) WP II Kepanjen, WP IV Tumpang serta WP V Turen dan Dampit dengan tingkat perkembangan sedang dan (3) WP III Ngantang dan WP VI Sumbermanjing Wetan dengan kondisi tingkat perkembangan rendah.Kata kunci. Pengembangan wilayah, pendekatan perwilayahan, tipologi wilayah, wilayah pengembangan.